2021
DOI: 10.1080/17538947.2021.1988163
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuous rock slope stability analysis by limit equilibrium approaches – a review

Abstract: Slope stability is one of the most important topics of engineering geology with a background of more than 300 years. So far, various stability assessment techniques have been developed which include a range of simple evaluations, planar failure, limit state criteria, limit equilibrium analysis, numerical methods, hybrid and high-order approaches which are implemented in two-dimensional (2D) and three-dimensional (3D) space. In the meantime, limit equilibrium methods due to their simplicity, short analysis time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 100 publications
0
26
0
Order By: Relevance
“…This indicates that the slope had completely slid off and attained its final stable state. The entire sliding process is similar to composite failure mode [33]. Comparing Figures 9b and 13 indicates that the simulated final stage was considerably closer to conditions during the actual landslide.…”
Section: Comparison Of the Numerical Simulation Results With Actual Rock Slope Failuresmentioning
confidence: 66%
“…This indicates that the slope had completely slid off and attained its final stable state. The entire sliding process is similar to composite failure mode [33]. Comparing Figures 9b and 13 indicates that the simulated final stage was considerably closer to conditions during the actual landslide.…”
Section: Comparison Of the Numerical Simulation Results With Actual Rock Slope Failuresmentioning
confidence: 66%
“…In some circumstances, the existence of an underground aquifer supplied by an upstream hydraulic recharge area may be a risk issue for such activity, as it is responsible for deep piezometric heads that can fluctuate seasonally [17]. Many researches have examined the mechanism of the influence of temperature and saturation on unsaturated clay slope stability in light of clay slope instability induced by ambient temperature and rainfall infiltration in summer and autumn [18,19]. The slope's factor of safety may be calculated by gradually diminishing the soil shear strength until the slope fails.…”
Section: Slope Stabilitymentioning
confidence: 99%
“…According to the effectiveness of the metaheuristics and their modified versions, these methods have been widely used to solve several geotechnical engineering problems, as presented in Table 1. In addition, a comprehensive review of slope stability analysis methods can be found in References [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%